ISOLATION OF CELLULOSE FROM SIWALAN FIBER (BORASSUS FLABELLIFER L.) USING RESPONSE SURFACE METHODOLOGY - AZAMI, YUSUF IKROM NUR; MUSFIROH, IDA; MUCHTARIDI; PRATIW, RIMADANI; PUTRA, OKTA NAMA (International Journal of Applied Pharmaceutics, 2023)
Objective: This study investigated the isolation of α-cellulose powder from siwalan fibers (Borassus flabellifer L.). Methods: The methods include delignification using 10% NaOH, and bleaching using 10% NaOCl. The present research used response surface methodology (RSM) to investigate the impact of temperature and duration on the bleaching process. Two factors were evaluated and optimized using the central composite design (CCD). Results: The findings revealed that the hit quality and white degree were 91.5% and 52.58% when the temperature and time of bleaching were 40 °C and 30 min, respectively. Utilizing an analysis of variance (ANOVA), the most influential factors on the percentage of strike quality and whiteness degree were identified. Absorption at 3323.34 cm-1 for O-H, 2893.22 cm-1 for C-H, 1371.38 cm-1 for C-O-H, and 1157.28 cm-1 for C-O, according to FTIR characterization results, are characteristic cellulose peaks. Conclusion: The cellulose characterization results acquired in this work show that the temperature in the bleaching process has a significant effect on the cellulose isolation results.